Design and Implementation of Small and Medium-Sized Financial Management Software - Guan, Shiwei (International Journal of Computer Science and Information Technology, 2025)
Currently, SMEs face challenges in financial software applications, such as high development difficulty, cost, closed system architecture, and limited scalability. To address these, we developed simple financial management software for SMEs using the Java programming language. We analyzed SMEs' financial processes and business needs to construct the system's interface framework and basic functional modules. The software's pages were designed and implemented using Java and MySQL database technology. Testing confirmed that the system is scientifically designed, fully functional, stable, and meets the practical financial needs of SMEs.